Students’ Perceptions of Using Falou Application to Improve Students’ Speaking Skills - Susi Sahmarito Rambe; Maryati Salmiah (Edumaspul: Jurnal Pendidikan, 2025)
This study explores English Department students' perceptions of using the Falou application to improve their English speaking skills through a descriptive qualitative approach. Three students from the English Department at Universitas Islam Negeri Sumatera Utara in Medan, North Sumatra, were selected using purposive sampling and interviewed using semi-structured interviews to examine their experiences with the application. Grounded in Mobile Assisted Language Learning (MALL) theoretical framework, the research addressed three key questions: students' perceptions of Falou's effectiveness, the most beneficial features, and challenges encountered during usage. Data analysis using thematic analysis revealed predominantly positive perceptions, with participants reporting increased confidence and improved speaking practice opportunities. The most effective features identified were pronunciation training with immediate feedback (94.4% positive rating), oral practice sessions with progressive structure (88.9%), conversation simulations providing realistic scenarios (88.9%), and comprehensive speaking assessments (77.8%). However, participants also faced significant technical challenges including audio quality fluctuations (61.1% reported concerns), network connectivity issues (61.1%), voice recognition delays (mixed ratings with only 38.9% positive), and severely limited offline access capabilities (only 5.6% found it adequate). The findings suggest that while mobile applications like Falou offer promising opportunities for autonomous English speaking practice among Indonesian university students, successful implementation requires robust technical infrastructure, comprehensive user support, and pedagogical design that addresses diverse learner needs in developing country contexts where internet connectivity remains inconsistent